2016
DOI: 10.1007/s10567-016-0218-x
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Technology-Based Youth and Family-Focused Interventions

Abstract: In the past 10 years, mental and behavioral health has seen a proliferation of technology-based interventions in the form of online and other computer-delivered programs. This paper focuses on technology-based treatment and preventive interventions aimed at benefitting children and adolescents via either involving the parents and families, or only the youth. The review considered only technology-based interventions that had at least one published study with a randomized controlled trial design. Questions being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
100
0
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(107 citation statements)
references
References 59 publications
3
100
0
4
Order By: Relevance
“…These programs are in different stages of implementation and validation, which was not assessed in this review. Previous metaanalysis or systematic reviews (Cushing & Steele, 2010;Hall & Bierman, 2015;MacDonell & Prinz, 2016) have already contributed to evaluate the effectiveness of technology-based programs targeting specific conditions, but more research is necessary. An optimistic perspective arises from the meta-analysis carried out by Wantland, Portillo, Holzemer, Slaughter, & McGhee (2004), which found that the use of web-based interventions for adults with chronic conditions showed larger effect sizes than the face-to-face programs in terms of the acquisition of knowledge and behaviour change.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These programs are in different stages of implementation and validation, which was not assessed in this review. Previous metaanalysis or systematic reviews (Cushing & Steele, 2010;Hall & Bierman, 2015;MacDonell & Prinz, 2016) have already contributed to evaluate the effectiveness of technology-based programs targeting specific conditions, but more research is necessary. An optimistic perspective arises from the meta-analysis carried out by Wantland, Portillo, Holzemer, Slaughter, & McGhee (2004), which found that the use of web-based interventions for adults with chronic conditions showed larger effect sizes than the face-to-face programs in terms of the acquisition of knowledge and behaviour change.…”
Section: Discussionmentioning
confidence: 99%
“…Mixed findings about the acceptability, parent engagement, and impact of these programs have been reported. Another review about family-focused mental health interventions found good evidence for the effectiveness of parent training using evidencebased parenting strategies through technologybased interventions (MacDonell & Prinz, 2016).…”
Section: Palavras-chave: Saúde; Tecnologia Da Informação; Responsabilmentioning
confidence: 99%
See 1 more Smart Citation
“…Driving the growth in telehealth interventions is the dual promise of increasing population 'reach' (i.e., overcoming many of the common barriers to in-person access) while decreasing delivery costs (Baker & Sanders, 2016;Hall & Bierman, 2015;Jones et al, 2013;Macdonell & Prinz, 2016). Despite the acknowledged potential of these emerging telehealth technologies, and the proliferation of teleheath interventions more broadly, there remain few empirically-validated parenting programmes currently available in an online or telehealth delivery modality (Baker & Sanders, 2016).…”
Section: Chapter 4 -The Research Protocol Of Tpol-d 39mentioning
confidence: 99%
“…With the success of any parenting programme depending on both the willingness of parents to engage, as well as the feasibility of such engagement, it is vital that consumer preference be used to inform online parenting intervention design Macdonell & Prinz, 2016).…”
Section: Assessing Consumer Preference In Telehealth-based Parent-tramentioning
confidence: 99%